Spatial distribution characteristics of heavy metal(loid)s health risk in soil at scale on town level - Cang Gong; Haichuan Lu; Zhixiang Zhang; Liang Wang; Xiang Xia; Lihua Wang; Zhiyu Xiang; Linyang Shuai; Yang Ding; Yong Chen; Shunxiang Wang (Scientific Reports, 2022)
Abstract In order to reveal the Spatial distribution characteristics of heavy metal(loid)s health risk in soil on the town-scale, 788 topsoil samples were collected from a town in the hinterland of Chengdu Plain, with 5 subordinate communities and 17 administrative villages as the research sub regions. The USEPA health risk assessment model was used to assess the health risks of heavy metal(loid)s Cd, Hg, As, Cu, Pb, Cr, Zn and Ni in the soil, the health risk analysis method system based on the geographic detector and the optimized rank-size theory model are used to clarify the spatial differentiation and risk level difference of health risk in the study area. The results showed that the average values of Cd, Hg, As, Pb, Cr, Cu, Ni and Zn in the soil of the study area were 0.221, 0.155, 9.76, 32.2, 91.9, 35.2, 37.1 and 108.8 mg/kg, respectively. The health risks of heavy metal(loid)s in soil to adults and children are generally within the acceptable range, but the maximum hazard index of children and the maximum non-carcinogenic risk value of Cr to children are 2.653303 and 1.213098 respectively, which were exceeding the acceptable range. The carcinogenic risk of Cr and As to adults and children and the carcinogenic risk of Cd to children are at 1 × 10–4 to 1 × 10–6, exceeding the 10–6 health threshold. The q-value range of heavy metal(loid)s health risk spatial differentiation of soil in the study area is 0.016–0.425. The spatial differentiation of non-carcinogenic risk of Hg, As, Ni, Pb, Cd and Cr and the spatial differentiation of carcinogenic risk of Cr and As are larger, which needs further attention. The strictly controlled area of heavy metal(loid)s health risk in the soil of the study area (R ≥ 1.1) is mainly concentrated in the central, western and northeast sub regions, and most sub regions belong to the safe utilization area (0.9 < R < 1.1). The health risk assessment of heavy metal(loid)s in soil on a town scale is of positive significance for enriching health risk research methods, measuring health risk levels at different scales, and formulating refined risk management and control strategies.